Inactivation of pathogenic microflora using ultraviolet excilamp in presence hydrogen peroxide - S A Astakhova; G G Matafonova; V B Batoev (RUDN Journal of Ecology and Life Safety, 2008)
The high inactivation efficiency of ultraviolet radiation of KrCl excilamp (222 nm) was obtained. Vegetative cells of Bacillus cereus, Escherichia coli O157:H7 at initial populations from 102 to 107 CFU ml-1 were treated by KrCl excilamp with and without H2O2.